FACE THREATENING ACTS USED BY THE MAIN CHARACTER OF “SHERLOCK HOLMES: A GAME OF SHADOWS” MOVIE - PUTERI, ARISTYA PRADHANI (Jurnal Ilmiah Mahasiswa FIB, 2014)
People need to communicate in conveying meaning and feeling to eachother. In conveying message, people sometimes perform acts which are able tothreat interlocutors. Politeness theory, in particular face threatening acts is used bythe writer in analyzing “Sherlock Holmes: The Game of Shadows” movie, becausethe writer wants to present the difference of face threatening acts usage betweentwo opposite relation; friend and adversary. There are two problems to be solved,they are: (1) What face threatening acts are performed by the main characters inSherlock Holmes: A Game of Shadows movie and (2) What types of politenessstrategies are performed by the main characters in Sherlock Holmes: The Game ofShadows movie.This study uses qualitative approach and it is included in documentanalysis because the writer‟s data is movie script. In analyzing the data, the writeronly chooses utterances containing FTA and politeness strategies. Then, the writermakes the conclusion/verification based on Brown and Levinson‟s theory.The result of this study suggests that there are 43 utterances containingFTAs. Out of the 43 utterances, 32 of them are realized in bald-on record and offrecord strategies, and the remaining ones -11 utterances- are performed withpoliteness strategies. The act which most frequently used is „order‟ whichperformed baldly. Moreover, politeness strategy mostly performed is „addressform” which is categorized in one of positive politeness strategies. The „addressform‟ used by the main character is show his intimacy with the hearer. For future research, the writer suggests to the next researcher to applystrategies of minimizing face threatening act in studying politeness from differentlanguage beside English. Keywords: Face Threatening Acts, Politeness Strategies, Sherlock Holmes: TheGame of Shadows Movie.